Quantifying the association between ethnicity and COVID-19 mortality: a national cohort study protocol. Issue 4 (7th April 2021) - Dambha-Miller, Hajira; Tan, Pui San; Saatci, Defne; Clift, Ashley Kieran; Zaccardi, Francesco; Coupland, Carol; Locufier, Patrick; Davies, Firoza; Khunti, Kamlesh; Griffin, Simon J; Hippisley-Cox, Julia
Abstract : Introduction: Recent evidence suggests that ethnic minority groups are disproportionately at increased risk of hospitalisation and death from SARS-CoV-2 infection. Population-based evidence on potential explanatory factors across minority groups and within subgroups is lacking. This study aims to quantify the association between ethnicity and the risk of hospitalisation and mortality due to COVID-19. Methods and analysis: This is a retrospective cohort study of adults registered across a representative and anonymised national primary care database (QResearch) that includes data on 10 million people in England. Sociodemographic, deprivation, clinical and domicile characteristics will be summarised and compared across ethnic subgroups (categorised as per 2011 census). Cox models will be used to calculate HR for hospitalisation and COVID-19 mortality associated with ethnic group. Potential confounding and explanatory factors (such as demographic, socioeconomic and clinical) will be adjusted for within regression models. The percentage contribution of distinct risk factor classes to the excess risks seen in ethnic groups/subgroups will be calculated. Ethics and dissemination: The study has undergone ethics review in accordance with the QResearch agreement (reference OX102). Findings will be disseminated through peer-reviewed manuscripts, presentations at scientific meetings and conferences with national and international stakeholders.